The Porticoes of Bologna and contemporary architecture. A proposal for a Minor Boundary Modification towards Kenzo Tange - Pretelli, Marco; Tolic, Ines (Restauro Archeologico, 2023)
After a long and complex process, the porticoes of Bologna were included in the UNESCO World Heritage List at the 44th session of the International Committee held in Fuzhou, China, on 16-31 July 2021. Among the aspects emphasised was the extraordinary adaptability of the asset, which has been intermediating public and private space since the 12th century. In the second half of the 20th century, the updating of technologies, materials and ways of living confirmed the importance of the portico even in the suburbs, leading to the construction of fine examples such as the one in the Barca district, designed by Giuseppe Vaccaro. Included in the UNESCO selection, on the one hand this portico courageously opens up to the contemporary, while on the other hand it imposes a reflection on the most recent interpretations of the asset. Among these, one should at least consider Kenzo Tange’s arcades at the Fiera District, which, due to their historical and urban value, deserve to be included in the UNESCO selection through a Minor Boundary Modification.